2021
DOI: 10.1155/2021/5185264
|View full text |Cite
|
Sign up to set email alerts
|

Active Aging through Volunteerism: A Longitudinal Assessment of Perceived Neighborhood Safety as a Predictor among Older Adults, 2008-2018

Abstract: Volunteering can play an important role in active aging. The resource theory of volunteering posits that volunteerism depends on human, social, and cultural capital. Benefits of volunteering have been documented at the micro-, meso-, and macrolevels, positively affecting individual older people as well as their local communities and society at large. Taking a process-oriented theoretical approach, this study focused on the mesolevel factor of the environment with the purpose of determining the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Detailed information on sampling design, survey content, and sample weights can be found elsewhere 26 . As a previous publication utilizing HRS data states, 27 every 2 years since 1992, the HRS has interviewed approximately 20,000 Americans aged 50 and older. Data are collected on various topics, including demographic characteristics, health behaviors and outcomes, employment status, wealth, and income.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on sampling design, survey content, and sample weights can be found elsewhere 26 . As a previous publication utilizing HRS data states, 27 every 2 years since 1992, the HRS has interviewed approximately 20,000 Americans aged 50 and older. Data are collected on various topics, including demographic characteristics, health behaviors and outcomes, employment status, wealth, and income.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the net width of the walk is greater than 1.2 m, and the local width is not less than 1.8 m as much as possible. The wind environment is relatively poor in the natural light environment (75), noise environment (72.22), and wind environment (66.67). In the future, we should improve the ventilation of buildings, use green plants flexibly, reduce the noise of domestic life scientifically, and simultaneously reduce light obstructions, such as sundries and nonbearing walls [72].…”
Section: Healthmentioning
confidence: 99%
“…In terms of self-improvement participation, volunteer activities have a slightly higher weight (0.512) than cultural activities (0.488). It has been demonstrated that volunteer service produces a good influence on older adults, their local communities, and the entire society [75]. AAT also emphasizes the significance and value of volunteer activities [76].…”
Section: Participationmentioning
confidence: 99%